Muscular dystrophies and myopathies: the spectrum of mutated genes in the Czech Republic - Stehlíková, Kristýna; Skálová, D; Zídková, J; Haberlová, Jana; Voháňka, Stanislav; Mazanec, Radim; Mrázová, Lenka; Vondráček, Petr; Ošlejšková, Hana; Zámečník, Josef; Honzík, T; Zeman, J; et al. (Clinical genetics, 2017)
Inherited neuromuscular disorder (NMD) is a wide term covering different genetic disorders affecting muscles, nerves, and neuromuscular junctions. Genetic and clinical heterogeneity is the main drawback in a routine gene-by-gene diagnostics. We present Czech NMD patients with a genetic cause identified using targeted next-generation sequencing (NGS) and the spectrum of these causes. Overall 167 unrelated patients presenting NMD falling into categories of muscular dystrophies, congenital muscular dystrophies, congenital myopathies, distal myopathies, and other myopathies were tested by targeted NGS of 42 known NMD-related genes. Pathogenic or probably pathogenic sequence changes were identified in 79 patients (47.3%). In total, 37 novel and 51 known disease-causing variants were detected in 23 genes. In addition, variants of uncertain significance were suspected in 7 cases (4.2%), and in 81 cases (48.5%) sequence changes associated with NMD were not found. Our results strongly indicate that for molecular diagnostics of heterogeneous disorders such as NMDs, targeted panel testing has a high-clinical yield and should therefore be the preferred first-tier approach. Further, we show that in the genetic diagnostic practice of NMDs, it is necessary to take into account different types of inheritance including the occurrence of an autosomal recessive disorder in two generations of one family.
Keywords: mutace; dospělí; Genetic Testing; Female; Adult; mladý dospělý; ženské pohlaví; High-Throughput Nucleotide Sequencing; svalové dystrofie; Muscular Diseases; nemoci svalů; Adolescent; Muscular Dystrophies; lidé; Mutation; Male; Czech Republic; vysoce účinné nukleotidové sekvenování; Young Adult; genetické testování; Sequence Analysis, DNA; Česká republika; mužské pohlaví; sekvenční analýza DNA; mladiství; Humans